Evaluating Wireless Communication Performance at Quarries - Kalpaxidou, Eleni; Vernersson, Susanne (My University, 2013)
The quarry industry and the material it provides such as sand, gravel and hard rock are often an overlooked resource to our modern society. Nevertheless, aggregates are found everywhere in our buildings and roads. In Europe alone there are over 24 000 quarries with an annual demand of 3 billion tonnes translating into a 20 billion Euro turnover. The quarry industry has an increasing potential in improving productivity and safety with the introduction of wireless communication technologies. This may however be a difficult task due to the harsh and constantly changing environment of the quarry with high EMC, vibrations, dust and solid materials. One of the major challenges will be to provide efficiency and reliability to applications based on the wireless communication. In recent years, great efforts have been made to increase road safety with vehicle-tovehicle and vehicle-to-infrastructure (V2V/V2I) communication in highly dense traffic scenarios. The proposed communication standard has so far been IEEE 802.11p for communicating vehicles with the use of a vehicular ad hoc network (VANET). Although large actors such as Volvo, Honda, Daimler and BMW are actively participating in the car-to-car communication (C2C) consortium, little time has been spent in investigating the possibilities of bringing intelligent transport systems (ITS) to the quarry industry. The main focus of this master thesis has therefore been to evaluate a set of suitable wireless technologies that successfully can be used in V2V/V2I communication in quarries. The technologies used in the evaluation included IEEE 802.15.4, ZigBee RF, IEEE 802.11g and IEEE 802.11p that is commonly used in V2V communication.
Keywords: Data- och informationsvetenskap; Informations- och kommunikationsteknik; Computer and Information Science; Information & Communication Technology